Sparkes, Rev. North River. Photograph of older woman with 5 children. - Sparkes, Rev.
Photo of Hubert Bradbury, sparkes , Grandmother Florence, Elizabeth Bradbury, Claudine Sparkes, Marjorie Sparkes, all grandchildren of Florence